2016
DOI: 10.1038/cddis.2016.311
|View full text |Cite
|
Sign up to set email alerts
|

Loss of XIAP facilitates switch to TNFα-induced necroptosis in mouse neutrophils

Abstract: Neutrophils are essential players in the first-line defense against invading bacteria and fungi. Besides its antiapoptotic role, the inhibitor of apoptosis protein (IAP) family member X-linked IAP (XIAP) has been shown to regulate innate immune signaling. Whereas the role of XIAP in innate signaling pathways is derived mostly from work in macrophages and dendritic cells, it is not known if and how XIAP contributes to these pathways in neutrophils. Here we show that in response to bacterial lipopolysaccharides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 59 publications
4
92
0
Order By: Relevance
“…It was shown that inflammatory mediator channels, cell junctions, and apoptotic process were closely related to the anti-inflammatory mechanism of FF. LPS is known to induce the secretion of inflammatory cytokines including IL-1β and COX-2 [17], which are closely associated with AKI [18]. Except for iNOS, NF-κB and IL-1β were detected in bioinformatics analysis, and other inflammatory-related cytokines including MCP-1, TNF-α, and COX-2 were also affected in an in vivo test.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that inflammatory mediator channels, cell junctions, and apoptotic process were closely related to the anti-inflammatory mechanism of FF. LPS is known to induce the secretion of inflammatory cytokines including IL-1β and COX-2 [17], which are closely associated with AKI [18]. Except for iNOS, NF-κB and IL-1β were detected in bioinformatics analysis, and other inflammatory-related cytokines including MCP-1, TNF-α, and COX-2 were also affected in an in vivo test.…”
Section: Discussionmentioning
confidence: 99%
“…There are various mutations found in all over the gene encoding XIAP, contributing to immune hyper-activation and tissue inflammation in XLP-2 patients (Prokop et al, 2017). To determine whether these mutations in XIAP cause sensitivity to TNFR2 induced cell death, we utilized the HoxB8 progenitor system (Wicki et al, 2016). Briefly, lineage negative cells from the bone marrow were transduced with 4-hydroxytamoxifen (4-OHT) inducible HoxB8 and immortalized with stem cell factors.…”
Section: Loss Of Xiap Ring Domain Sensitizes Macrophages and Neutrophmentioning
confidence: 99%
“…However, differentiated xiap -/granulocytes were sensitive to TNFR2 induced cell death but not to TR1-TNF ( Figure 1E). To assess the contribution of either the BIR or RING domain of XIAP to the observed cell death, different XIAP constructs containing mutations found in XLP-2 patients were re-introduced into the HoxB8 progenitor cells (Wicki et al, 2016) (Figure 1F). Xiap -/-HoxB8 granulocytes with XIAP wildtype reintroduced (xiap +/+ ) remained insensitive to either TR1-or TNC-TNF induced cell death ( Figure 1G).…”
Section: Loss Of Xiap Ring Domain Sensitizes Macrophages and Neutrophmentioning
confidence: 99%
See 2 more Smart Citations